Komparasi Alih Daya Undang-Undang Ketenagakerjaan dengan Undang-Undang Cipta Kerja Tahun 2023 - Febrianti, Lidia; Sambah, Thamrin; Seruni, Puti Mayang (Universitas Semarang, 2023)
This research aims to compare the concept of outsourcing in the Law number 13 of 2003 concerning Manpower (Manpower law) compared to the Law Number 6 of 2023 concerning Job Creation (Job Creation Law 2023). This research is important because the Job Creation Law 2023 eliminates job restrictions that are permitted in the outsourcing system. This change is contrary to the workers' desire to eliminate the concept of outsourcing which is considered detrimental to workers. This research uses a type of normative research that relies on secondary data consisting of primary legal materials (law and regulations), secondary legal materials (books and research articles), and tertiary legal materials (encyclopedias and dictionaries). The data was analyzed qualitatively and conclusions were drawn using deductive logic. In general, this research produces new findings in the form of conceptual differences between outsourcing in the Employment Law and the 2023 Job Creation Law. Different concepts will bring different practices accompanied by positive and negative effects. The results of this research show that there is a significant change in the concept of outsourcing in the Job Creation Law 2023, eliminating restrictions so that types of work are more flexible. This opens up opportunities for companies to be able to outsource all sectors of their work, including those that are in their ‘core business’ field. Currently, there is no longer a distinction between ‘work contract agreement’ (perjanjian penyediaan pekerjaan) or ‘worker service provision agreement’ (perjanjian penyediaan jasa pekerja) as regulated in the Manpower Law. There are still options in the work agreement basis for outsourcing, the agreement can be in the form of PKWTT or PKWT. If implemented with PKWT it must be accompanied by a transfer of undertaking protection of employment (TUPE). Penelitian ini bertujuan untuk melihat perbandingan mengenai konsep alih daya dalam UU Ketenagakerjaan dibandingkan dengan UU Cipta Kerja Tahun 2023. Peneltiian ini penting dilakukan sebab UU Cipta Kerja Tahun 2023 menghilangkan batasan-batasan pekerjaan yang diperbolehkan dalam sistem alih daya. Perubahan ini bertolak belakang dengan keinginan para pekerja selama ini untuk menghilangkan konsep alih daya yang dianggap merugikan pekerja. Penelitian ini menggunakan jenis penelitian normatif yang bertumpu pada data sekunder yang terdiri dari bahan hukum primer yakni peraturan perundang-undangan , bahan hukum sekunder yakni hasil penelitian dan bentuk literasi lainnya, dan bahan hukum tersier yang diperoleh dari ensiklopedia dan kamus hukum. Data kemudian dianalisis secara kualitatif dan kesimpulan ditarik dengan logika deduktif. Penelitian ini secara garis besar menghasilkan temuan baru berupa perbedaan konsep antara alih daya dalam UU Ketenagakerjaan dengan UU Cipta Kerja Tahun 2023. Konsep yang berbeda akan membawa praktik yang berbeda disertai dengan sisi positif dan sisi negatif. Hasil penelitian ini menunjukan bahwa terdapat perubahan konsep yang signifikan mengenai alih daya dalam UU Cipta Kerja Tahun 2023 menghilangkan batasan sehingga lebih fleksibel jenis pekerjaanya. Ini membuka peluang bagi perusahaan untuk dapat mengalih dayakan semua sektor pekerjaanya, termasuk yang menjadi core business-nya. Selain itu saat ini tidak lagi dikenal pemisahan antara “perjanjian pemborongan pekerjaan” atau “perjanjian penyediaan jasa pekerja” seperti yang diatur dalam UU Ketenagakerjaan. Basis perjanjian kerja yang boleh digunakan dalam alih daya masih terdapat opsi dengan PKWTT maupun dengan PKWT. Apabila dilaksanakan dengan PKWT harus disertai dengan pengalihan pelindungan hak pekerja.